Survey of the leg exocrine glands in termites(Isoptera) - Soares, Helena Xavier [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Sociedade Brasileira de Entomologia, 2002)
A survey of the leg exocrine glands in the termite workers of 16 species of the families Kalotermitidae and Termitidae was carried out through scanning electron microscope. Glandular openings were not found in the legs of Anoplotermes sp., Ruptitermes sp. (Apicotermitinae, Termitidae) or Glyptotermes planus (Kalotermitidae), but they are present, spread over the ventral surface of the first, second and third tarsomeres of other Termitidae such as Armitermes euamignathus, Cornitermes cumulans, Nasutitermes coxipoensis, Rhynchotermes nasutissimus, Syntermes nanus, Embiratermes festivellus (Nasutitermitinae), Amitermes beaumonti, Hoplotermes amplus, Microcerotermes sp., Neocapritermes opacus, Orthognathotermes sp., Spinitermes brevicornutus and Termes sp. (Termitinae). The pores are usually isolated but they can also be grouped inside a round depression. The occurrence of leg exocrine glands in the family Termitidae is reported for the first time.
Keywords: Exocrine gland; leg; morphology; scanning electron microscopy; termite